Basic researchBiochemical changes representing oxidative stress on brain tissue due to intraabdominal hypertension in a rat model - Karabekir, Hamit S.; Guzey, Feyza K.; Balci, Canan; Guvenc, Yesim; Onur, Ece; Akbulut, Gokhan; Serteser, Mustafa (Archives of Medical Science, 2007)
Introduction: Intraabdominal hypertension affects the central nervous system in addition to respiratory, renal and cardiovascular systems. This effect that, investigated in detail by clinical and experimental studies, is due to the increase of intracranial pressure and decrease of cerebral perfusion pressure caused by the increase of intrathoracic pressure and increase of pressure of great veins. However, no study has been found on biochemical changes on central nervous tissue due to intraabdomial hypertension. Material and methods: Thirty rats were divided into three groups containing 10 animals: sham group, study group I and study group II. In group I, intraabdominal pressure was elevated to 20 mmHg, and in group II, it was elevated to 30 mmHg for 60 minutes. Intracranial pressures (ICP) in all animals were monitored. Values of biochemical parameters including thiobarbituric acid, nitrite oxide, xanthine oxidase, protein carbonyls and protein sulfhydryl in cortical, subcortical, cerebellar and spinal cord tissues were compared with the corresponding values in sham rats. Results: Thiobarbituric acid (0.58±0.8 and 0.76±0.04 vs. 0.23±0.03, p<0.05 and p<0.001), nitrite oxide (3.11±0.10 and 8.46±0.54 vs. 1.52±0.18, p<0.05 and p<0.001), xantine oxidase (1.55±0.11 and 3.01±0.25 vs. 0.32±0.09, p<0.001) and carbonyl levels (1.41±0.01 and 1.69±0.01 vs. 1.22±0.03, p<0.001) of the various central nervous system regions and ICP were increased. SH levels (92.60±2.50 and 74.60±3.80 vs. 139.20±4.72, p<0.001) were decreased after intraabdominal hypertension, and higher IAP generally caused more detrimental effects on these parameters. The levels of spinal cord and cerebellum samples were significantly worse in the study groups for most of the markers. Conclusions: Intraabdominal hypertension may cause biochemical changes representing oxidative stress on various regions of central nervous system even 60 minutes after increase of intraabdominal pressure, and higher IAH causes more detrimental effects. Most prominent effects were seen in spinal cord and cerebellar tissue suggesting that compression of lumbar vertebral venous pressure might have a role in addition to increase of ICP due to increase of pressure of great veins caused by increase of intrathoracic pressure.